2022
DOI: 10.34123/icdsos.v2021i1.136
|View full text |Cite
|
Sign up to set email alerts
|

Working Age Population and CO2 Emissions in Indonesia:

Abstract: An increase in the working age population causes an increase in consumption which in turn will have an impact on increasing CO? emissions. The household is an element that must be responsible for increasing emissions of greenhouse gases because of their fossil fuels consumption. This study aims to observe the relationship of the working age population and the CO? emissions in households. This study use data from National Socio-Economic Survey (Susenas) 2019 with households consuming gasoline / diesel / kerosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…Although in the current study, age group does not correlate with significant differences in total carbon emissions, the young adult and middle-aged group's (25-59 years) carbon emissions were greater than those of the younger age group (13-24 years) and the elderly group (65-74 years). This finding is consistent with a study in the Indonesian working age population that demonstrated that productive age groups (15-59 years) produced higher total carbon emissions than the non-productive age groups (0-15 years and over 65 years) [3]. The current study's finding seems to contradict with other study in the urban household at Yangtze River Delta, China, which showed that carbon emissions will increase slightly as people get older [47].…”
Section: Plos Onesupporting
confidence: 80%
See 4 more Smart Citations
“…Although in the current study, age group does not correlate with significant differences in total carbon emissions, the young adult and middle-aged group's (25-59 years) carbon emissions were greater than those of the younger age group (13-24 years) and the elderly group (65-74 years). This finding is consistent with a study in the Indonesian working age population that demonstrated that productive age groups (15-59 years) produced higher total carbon emissions than the non-productive age groups (0-15 years and over 65 years) [3]. The current study's finding seems to contradict with other study in the urban household at Yangtze River Delta, China, which showed that carbon emissions will increase slightly as people get older [47].…”
Section: Plos Onesupporting
confidence: 80%
“…Fourth, the selection of two study areas by purposive sampling who have the highest level of air pollution in Jakarta [11] can not generalize and represent the study results at Jakarta and Indonesia levels. However, characteristic of Indonesian communities carbon emissions in the current study was almost similar with Indonesian National Economic Survey (SUSENAS) [3], i.e. transportation sector affected the community carbon emissions.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations